Human herpesvirus-6 infection in a critically ill and immunocompetent patient: a case report - Xin Tian Chia; Hai Liang Marc Wong; Jia Shen Loh (Journal of Medical Case Reports, 2024)
Abstract Background Human herpesvirus-6 is a rare infection in an immunocompetent adult. In existing literature, there is a dearth of knowledge that mainly exists as case reports and case series. Case Presentation In this case report, we described a 29-year-old female of Myanmarese descent patient from Myanmar who presented with altered mental status and non-specific respiratory and gastrointestinal symptoms. She was initially treated for pneumonia and discharged well. However, she re-presented to the hospital and was subsequently treated for severe central nervous system infection. Cerebrospinal fluid studies detected human herpesvirus-6 polymerase chain reaction with associated high serum human herpesvirus-6 concentration. This infection also triggered hemophagocytic lymphohistiocytosis. Treatment was initiated against both human herpesvirus-6 infection and hemophagocytic lymphohistiocytosis, and she responded to antiviral treatment and steroids, respectively. Conclusion This case study highlights the need for prompt diagnosis and treatment of this severe disease and the dangerous complications. Additionally, the authors share insights on the diagnostic challenges faced in the treatment of this patient.